Liquid-liquid equilibrium for the ternary system of (2-methyl-2-butanol + water + n-octanol) at different temperatures. (October 2021) - Zhang, Xuemei; Yang, Feiyan; Jian, Chungui; Wang, Hongwei; Kong, Wangxin; Shangguan, Guangjin; Xia, Meifang
Highlights: Liquid-liquid equilibrium (LLE) data for the ternary system of 2-methyl-2-butanol + water + n -octanol were determined at 303.15 K, 313.15 K, and 323.15 K under atmospheric pressure. The Othmer-Tobias and Hand equations were selected to test the reliability of the experimental LLE data, and the correlation coefficient ( R 2 ) is close to 1. The selectivity ( S ) was used to evaluate the capacity of n -octanol to extract 2-methyl-2-butanol from the mixture of 2-methyl-2-butanol and water, which is greater than 119. The NRTL and UNIQUAC models were applied to correlate the experimental LLE data, and the binary interaction parameters were obtained. The root-mean square deviations (RMSDs) for the two models obtained are less than 1.1%. Abstract: Liquid-liquid equilibrium (LLE) data for the ternary system of (2-methyl-2-butanol + water + n -octanol) were determined at 303.15 K, 313.15 K, and 323.15 K under atmospheric pressure. The Hand equation, the Othmer-Tobias equation, and the mass balance between the feed and the conjugated phases were used to test the reliability of the experimental LLE data. The results show that the correlation coefficients ( R 2 ) of the equations are close to 1, and the relative error of mass balance is less than 0.5%. The selectivity ( S ) was used to evaluate the capacity of n -octanol to extract 2-methyl-2-butanol from the water, which is much greater than 1. Furthermore, S decreases with the mass fraction of 2-methyl-2-butanol in the aqueous phase and increases with equilibrium temperature. The NRTL and UNIQUAC models were applied to correlate the experimental LLE data, and the binary interaction parameters were obtained. The root-mean square deviations (RMSDs) for the two models obtained are less than 1.1%.